Vaccinations in prison settings: A systematic review to assess the situation in EU/EEA countries and in other high income countries. Issue 35 (14th August 2019) - Madeddu, Giordano; Vroling, Hilde; Oordt-Speets, Anouk; Babudieri, Sergio; O'Moore, Éamonn; Noordegraaf, Marije Vonk; Monarca, Roberto; Lopalco, Pier Luigi; Hedrich, Dagmar; Tavoschi, Lara
Abstract: Introduction: In 2016, more than 600, 000 persons were being held in EU/EEA correctional facilities on a given day. People in prison may be at risk of vaccine-preventable diseases. While vaccination recommendations for people in prison exist, little is known on coverage and implementation options. Methods: We performed a systematic review on existing evidence on vaccination in prison settings in the EU/EEA. We searched peer-reviewed and grey literature following international methodology and reporting standards, to gather records published between 1980 and 2016 in all languages. We analysed quantitative (acceptance, uptake, cost-effectiveness) and qualitative (barriers) outcomes. Results: Out of 7041 identified records, 19 full-text articles were included from peer-reviewed literature and two from grey literature. Of these, 18 reported on hepatitis A and/or B virus (HAV/HBV), two on influenza and one on MMR vaccination. Two studies on HAV vaccine reported varying acceptance (5–91%) and uptake rates (62.9–70.5%). Seven studies reported on HBV vaccination. A comparative study showed a significantly higher uptake of the third HBV vaccine dose with the very rapid (63%) compared to the standard schedule (20%). HBV vaccination was generally well accepted (54–100%), whereas uptake was variable (dose 1:23–100%, dose 2:48–92%, dose 3:19–80%). One study on the combined HAV/HBV vaccine reported an acceptance rate of 34%, and declining uptake following dose 1. One study on influenza vaccine showed an uptake of 42–46%, while another reported a MMR vaccine acceptance of 80% and an uptake of 74%. Overall, main reasons for non-vaccination included release from/or transfer between prisons, and refusal. Conclusions: This systematic review highlighted important knowledge gaps and operational challenges for vaccination in prison settings. Vaccination is an effective measure that warrants comprehensive and tailored implementation to reduce the preventable disease burden, avoid risks of large outbreaks of vaccine-preventable diseases, and contribute to health equity for people in prison.